Burden of mortality linked to community-nominated priorities in rural South Africa - Pyry Mattila; Justine Davies; Denny Mabetha; Stephen Tollman; Lucia D’Ambruoso (Global Health Action, 2022)
Background Community knowledge is a critical input for relevant health programmes and strategies. How community perceptions of risk reflect the burden of mortality is poorly understood. Objective To determine the burden of mortality reflecting community-nominated health risk factors in rural South Africa, where a complex health transition is underway. Methods Three discussion groups (total 48 participants) representing a cross-section of the community nominated health priorities through a Participatory Action Research process. A secondary analysis of Verbal Autopsy (VA) data was performed for deaths in the same community from 1993 to 2015 (n = 14,430). Using population attributable fractions (PAFs) extracted from Global Burden of Disease data for South Africa, deaths were categorised as ‘attributable at least in part’ to community-nominated risk factors if the PAF of the risk factor to the cause of death was >0. We also calculated ‘reducible mortality fractions’ (RMFs), defined as the proportions of each and all community-nominated risk factor(s) relative to all possible risk factors for deaths in the population  . Results Three risk factors were nominated as the most important health concerns locally: alcohol abuse, drug abuse, and lack of safe water. Of all causes of deaths 1993–2015, over 77% (n = 11,143) were attributable at least in part to at least one community-nominated risk factor. Causes of attributable deaths, at least in part, to alcohol abuse were most common (52.6%, n = 7,591), followed by drug abuse (29.3%, n = 4,223), and lack of safe water (11.4%, n = 1,652). In terms of the RMF, alcohol use contributed the largest percentage of all possible risk factors leading to death (13.6%), then lack of safe water (7.0%), and drug abuse (1.3%)     . Conclusion A substantial proportion of deaths are linked to community-nominated risk factors. Community knowledge is a critical input to understand local health risks.